Pre-testing of Genetic Literacy Questionnaire Reveals Genetics Misconceptions Among Medical Students of Universitas Riau (Nusantara Science and Technology Proceedings, 2022)
Rapid advancement in genetics and genomics translates to its increasing relevancy in many sectors, including healthcare. In order to fully utilized genetic and genomic technologies in medicine, physicians, starting from medical students, need to have a good understanding on the subject. This study aimed to conduct genetic literacy questionnaire pre-testing on medical students of Universitas Riau. The International Genetic Literacy and Attitudes Survey (iGLAS) questionnaire was translated into Indonesian language. The initial translation was discussed in an expert review for construct validity as well as a student’s cognitive interview to review the language. Finally, internal consistency was tested on 34 students. The translated questionnaire had good construct validity. Review and interview suggested some wording changes to increase language understandability. The respondents had relatively low genetic literacy with mean score of 50.44 ± 11.57. The students had good knowledge regarding DNA nucleotides (70.6% correct answers) and function of a gene (97.1% correct answers). However, students overestimated the number of genes in human DNA (17.6% correct answers). We also found misconceptions regarding the term “genome” as all genes composition instead of all DNA sequences (32.4% correct answers). While the students know there are 23 chromosomes in human (73.5% correct answers), they misunderstood that each gene had 23 copies instead of 2 (23.5% correct answers). Other misconceptions were about genetic similarity between different cell types of an individual (20.6% correct answers), between family member (38.2% correct answers), and between random people (only one answered correctly, 2.9%). This result could lay the basis for intervention to increase genetic literacy among medical students.